PENINGKATAN KEMAMPUAN BERBAHASA ANAK USIA DINI MELALUI METODE BERCERITA DENGAN BONEKA TANGAN PADA KELOMPOK A DI BA AISYIYAH JOTON I JOGONALAN KLATEN - Imas Hartati; Umi Faizah (STPI Bina Insan Mulia Yogyakarta, 2022)
The problem's background was the low language skill for the children in group A in BA Aisyiyah Joton I Jogonalan Klaten. This can be seen from the limited use of vocabulary in children so that the child cannot speak properly. The formulation of the problems in this research are: 1) how to apply the storytelling method by using hand puppets to improve the language skills of early childhood. 2) how to improve the language skills of early childhood through the application of the storytelling method by using hand puppets. The purpose of this research are: 1) to determine the application of the storytelling method by using hand puppet media in improving early childhood language skills. 2) to determine the increase in language skills of early childhood through the application of the storytelling method using hand puppet media. The research method used in this research is Classroom Action Research (CAR) which is carried out in 2 cycles, each cycle consisting of four components, namely planning, implementing, observing, and reflecting. The data collection techniques used were observation, interview, and documentation. The research subjects were group A, the students at BA Aisyiyah Joton I, the academic year 2020/2021, totaling 10 children.The research results indicate that: 1) the application of the storytelling method by using hand puppets was carried out in the following stages: a) preparation, b) class conditioning, c) storytelling activities, d) question and answer and appreciation, e) conducting an assessment through observation of indicator items. 2) In the pre-cycle, the language skills of the children from group A were 30%, and when the first cycle was carried out, the children's language skills could increase to 60% then in the second cycle it increased to 76%. So it can be concluded that the increase in children's language skills with the storytelling method by using hand puppet media increased by 40%.